Patients with Epididymo-Orchitis and Meteorological Impact in Taiwan: A Nationwide Population-Based Study. (20th February 2017) - Liu, Jui-Ming; Chang, Ying-Hsu; Ho, Te-Wei; Chang, Fung-Wei; Pang, See-Tong; Hsu, Ren-Jun; Lin, Po-Hung
Abstract : Background . Epididymo-orchitis is a common infectious disease among men, especially men aged 20 to 39 years. The aim of this study was to analyze possible associations of various meteorological indicators on the incidence of epididymo-orchitis in Taiwan. Methods and Materials . This nationwide population-based study collected data on cases of epididymo-orchitis that were newly diagnosed from 2001 to 2013 in Taiwan. Monthly meteorological indicators, including average temperatures, humidity, rainfall, total rain days, and sunshine hours, were collected from the Central Weather Bureau of Taiwan. Data for a total of 7, 233 patients with epididymo-orchitis were collected for this study. Results . The monthly incidence of epididymo-orchitis was positively correlated with temperature, rainfall, and sunshine hours. The average monthly temperature had a linear correlation with the incidence of epididymo-orchitis (ß = 0 . 11 ). The monthly average temperature is significantly related, with a positive linear correlation, to the incidence of epididymo-orchitis in Taiwan. Conclusion . This finding may constitute useful information in terms of helping physicians to distinguish between patients with epididymo-orchitis and testicular torsion in hot or cold weather.